THE EFFECT OF TIME-RESTRICTED EATING (TRE) COMBINED WITH ENERGY RESTRICTION ON WEIGHT LOSS AND CARDIOMETABOLIC MARKERS IN OVERWEIGHT/OBESE SUBJECTS: A SYSTEMATIC REVIEW - Bertrand Hutagalung; Grace Joselini Corlesa; Astheria Eryani; Diana Listy L. P. Nababan; Joseph Bagasjati Pradika; Kamal Yasin; Nur Khalisa Yahya (Journal of Innovation Research and Knowledge, 2026)
Background:The global prevalence of overweight and obesity has escalated to alarming, epidemic levels, solidifying its role as a primary and significant risk factor for major cardiometabolic diseases. Time-Restricted Eating (TRE), which operates by simply confining food intake to a limited daily window, has recently emerged as a popular and flexible dietary strategy. However, a crucial question remains: we must systematically examine the true efficacy of TRE when deliberately combined with Energy Restriction (ER), particularly when directly compared against the established Conventional Energy Restriction (CER) diet. Purpose:The primary objective of this systematic review is to determine the efficacy and compare the outcomes of two dietary strategies, namely TRE combined with ER versus CER, in an adult population with overweight and obesity. The primary outcome assessed is weight loss, while secondary outcomes focus on improvements in cardiometabolic markers. Methods:This systematic review was conducted on randomized controlled trials (RCTs) comparing TRE+ER interventions with CERs that had similar calorie deficits. The main inclusion criteria involved adult subjects who were overweight or obese. The primary outcome analyzed was Weight Loss, while secondary outcomes included cardiometabolic markers such as HOMA-IR, fasting glucose, and lipid profile. Results:In general, TRE+ER has been shown to produce weight loss (such as BMI and fat mass) comparable to CER. However, when analyzing meal timing, Early TRE (eTRE) showed significant advantages in improving insulin sensitivity (HOMA-IR), indicating additional metabolic benefits of synchronizing meal timing with the body's biological clock. Conclusions: TRE combined with energy restriction is an effective dietary alternative comparable to CER for weight management. We recommend prioritizing Early TRE because it provides superior benefits in improving insulin resistance, making it an ideal strategy for the prevention and management of cardiometabolic risk.